2012
DOI: 10.1021/jm300662d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel N-Branched Acyclic Nucleoside Phosphonates As Potent and Selective Inhibitors of Human, Plasmodium falciparum and Plasmodium vivax 6-Oxopurine Phosphoribosyltransferases

Abstract: Hypoxanthine-guanine-(xanthine) phosphoribosyltransferase (HG(X)PRT) is crucial for the survival of malarial parasites Plasmodium falciparum (Pf) and Plasmodium vivax (Pv). Acyclic nucleoside phosphonates (ANPs) are inhibitors of HG(X)PRT and arrest the growth of Pf in cell culture. Here, a novel class of ANPs containing trisubstituted nitrogen (aza-ANPs) has been synthesized. These compounds have a wide range of K(i) values and selectivity for human HGPRT, PfHGXPRT, and PvHGPRT. The most selective and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 27 publications
0
74
0
Order By: Relevance
“…In addition, synthesis of six new aza-ANPs (4g, 4h, 4j and 5g, 5h, 5j) complementing the previously prepared 14,15 inhibitors of Pf, Pv and human HG(X)PRT is described, and their inhibitory activity (PfHGXPRT and human HGPRT) is reported to extend our published data. According our recent findings, phenylalanine prodrugs are more stable in plasma and their higher lipophilicity enable better penetration to the cells compared to alanine used in antivirals.…”
Section: Figmentioning
confidence: 65%
“…In addition, synthesis of six new aza-ANPs (4g, 4h, 4j and 5g, 5h, 5j) complementing the previously prepared 14,15 inhibitors of Pf, Pv and human HG(X)PRT is described, and their inhibitory activity (PfHGXPRT and human HGPRT) is reported to extend our published data. According our recent findings, phenylalanine prodrugs are more stable in plasma and their higher lipophilicity enable better penetration to the cells compared to alanine used in antivirals.…”
Section: Figmentioning
confidence: 65%
“…[5][6][7][8][9] Importantly, the mode of action of the ANPs is different from the currently used drugs, so represents a new approach to developing antimalarial therapeutics. An efficient synthetic methodology to access the desired 6-oxopurine ANPs with the (1H-1,2,3-triazol-4-yl)phosphonic acid moiety has been developed and optimized.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…1) and aza-ANPs ( Fig. 1) have antimalarial [5][6][7][8][9] and/or antimycobacterial [10][11] activity. Several different chemical types of ANPs, including modified PMEA analogues, have also been studied as potent inhibitors of bacterial adenylate cyclases, namely adenylate cyclase toxin from Bordetella pertussis and edema factor from Bacillus anthracis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of different structural analogues of these phosphonate inhibitors have been synthesised, including the single chain ANPs, the ANbPs, the aza-ANPs, the pyrrolidine nucleoside phosphonates, the pyrrolidine nucleoside bisphosphonates and the acylic immucillin phosphonates. 24,25,26,27,28 The crystal structures of the single chain ANPs in complex with HG[X]PRT [20] suggested that the attachment of a second phosphonate group to the basic ANP scaffold may allow a single molecule to occupy three critical binding pockets in the active site. These include the sites for the purine base, the 5′-phosphate group and, possibly, the pyrophosphate product (Fig.…”
Section: Introductionmentioning
confidence: 99%